GIS-material for the archaeological project: Rebuilding of existing pace track in Himmelstalund - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
By request of the County Administrative Board in Östergötland and due to a planned rebuilding of an existing pace track, the Swedish National Heritage Board's Contract Archaeology Service, UV Öst, has performed a field evaluation in Himmelstalund, Gamla Eneby, Borg parish, Norrköping municipality. The evaluation showed that the development area does not contain any traces of prehistoric or historical activity. The area has been partly destroyed in connection with the construction of the pace track, and no further archaeological measures will thus be taken prior to development.

Purpose:

The information in the purpose is translated from the archaeological report:
The purpose of the field evaluation, performed as a watching brief, was to determine whether any archaeological remains were going to be affected by the development plans, and particularly to determine whether any remains of the medieval village were preserved underneath the pace track. Also, the flat rock surfaces in the area were examined, in order to avoid damage to any unknown rock carvings.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
På uppdrag av Länsstyrelsen i Östergötland har Riksantikvarieämbetet UV Öst genomfört en förundersökning i form av antikvarisk kontroll inom Himmelstalund, Gamla Eneby tomt, Borgs socken, Norrköpings kommun. Förundersökningen föranleddes av en planerad ombyggnad av befintlig passbana.
Vid den arkeologiska förundersökningen konstaterades att den aktuella exploateringsytan inte visar några bevarade spår av förhistorisk eller historisk aktivitet. Området har delvis förstörts vid byggnationen av den befintliga passbanan och bedöms ur arkeologisk synvinkel vara klart för exploatering.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med den arkeologiska förundersökningen i form av antikvarisk kontroll, var att utröna om en fast fornlämning berörs av det planerade exploateringsprojektet och framför allt i det här fallet avgöra huruvida några lämningar efter den medeltida bytomten fortfarande kunde påträffas under passbanan. Vidare undersöktes de berghällar som påträffades, så att inga okända hällristningar skulle sprängas bort i samband med passbanans ombyggnad.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Ombyggnad av befintlig passbana inom Himmelstalund
Keywords: HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi